Tunable second harmonic generation by an all-dielectric diffractive metasurface embedded in liquid crystals. (1st April 2022) - Rocco, Davide; Zilli, Attilio; Ferraro, Antonio; Borne, Adrien; Vinel, Vincent; Leo, Giuseppe; Lemaître, Aristide; Zucchetti, Carlo; Celebrano, Michele; Caputo, Roberto; De Angelis, Costantino; Finazzi, Marco
Abstract: We experimentally demonstrate the possibility to modulate the second harmonic (SH) power emitted by nonlinear AlGaAs metasurfaces embedded in a liquid crystal (LC) matrix. This result is obtained by changing the relative in-plane orientation between the LC director and the linear polarization of the light at the excitation wavelength. According to numerical simulations, second-harmonic is efficiently radiated by the metasurfaces thanks to the sizeable second-order susceptibility of the material and the resonant excitation of either electric or magnetic dipole field distributions inside each meta-atom at the illuminating fundamental wavelength. This resonant behavior strongly depends on the geometric parameters, the crystallographic orientation, and the anisotropy of the metasurface, which can be optimized to modulate the emitted SH power by about one order of magnitude. The devised hybrid platforms are therefore appealing in view of enabling the electrical control of flat nonlinear optical devices.